A Comparative Study of the Concept of the Child in the UN Convention on the Rights of the Child 1989 and Vietnamese Law - Duc, Nguyen Tien (VNU Journal of Science: Legal Studies; Vol 37 No 3, 2021)
30 years since the inception of the United Nations Convention on the Rights of the Child of 1989, the understanding of the international community towards the legal status of children has witnessed many profound changes. One of the Convention’s great achievements is to bring about a uniform concept of the child. The article throws some light on legal aspects of this definition under the Convention. Against that backdrop, it will analyze, compare and evaluate the compatibility of Vietnam’s laws relating to children’s rights. Keywords: Children; childhood; children’s rights; the U.N. Convention on the Rights of the Child.